1994
DOI: 10.1029/94jd01829
|View full text |Cite
|
Sign up to set email alerts
|

CH3OCI: UV/visible absorption cross sections, J values and atmospheric significance

Abstract: The UV/visible absorption spectrum of CH3OC1 has been measured at wavelengths between 200 and 460 nm and used to calculate photodissociation lifetimes in the stratosphere. At zenith angles between 80 ø and 90 ø and at a pressure of 100 mbar the lifetime with respect to photodissociation is of the order of 4 hours. The possible fate of CH3OC1 in the stratosphere is discussed and analogies are drawn with HOC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 26 publications
4
42
0
Order By: Relevance
“…Recent calculations on methylhypochlorite CH 3 OCl and chloromethanol ClCH 2 OH (11, 12) using this ccp-VDZ + sp basis set have been very successful. The values obtained are in reasonable agreement with the results both of more extensive computations (9) and of experimental findings (6)(7)(8).…”
Section: Choh To Its Electronic Excited States and Comparison Betweensupporting
confidence: 91%
See 1 more Smart Citation
“…Recent calculations on methylhypochlorite CH 3 OCl and chloromethanol ClCH 2 OH (11, 12) using this ccp-VDZ + sp basis set have been very successful. The values obtained are in reasonable agreement with the results both of more extensive computations (9) and of experimental findings (6)(7)(8).…”
Section: Choh To Its Electronic Excited States and Comparison Betweensupporting
confidence: 91%
“…In addition to the well-known reaction channel leading to the formation of CH 3 O and ClOO Helleis et al (5) found a second reaction channel forming methylhypochlorite CH 3 OCl. The electronic spectrum and possible photofragmentation processes of CH 3 OCl are subject of many recent experimental (6)(7)(8) and theoretical studies (9,10). The corresponding authors generally conclude that chlorine-substituted hydrocarbons play an important role in atmospheric chemistry as a possible chlorine reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…The dominant source of HO x radicals under the conditions of the polar lower stratosphere in late winter and early spring is not the production of O( 1 D) radicals through ozone photolysis with subsequent reaction with H 2 O, but rather the radical channel of the photolysis of CH 2 O (Reaction R14) Crowley et al, 1994). Thus, the photolysis of CH 2 O (radical channel) is effectively driving the depletion of HCl.…”
Section: The Path To Full Activation Of Hclmentioning
confidence: 99%
“…This can be evaluated through examination of the ultraviolet (UV) absorption spectrum of CH 3 OCl. Crowley et al 12 characterized the UV absorption spectrum of gas-phase CH 3 OCl from 200 to 460 nm. A study by Jungkamp et al 13 CH 4 + Cl f CH 3 12 The absorption spectrum exhibited two peaks in the UV range, one centered at 235 nm and a weaker one peaking at 310 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Crowley et al 12 characterized the UV absorption spectrum of gas-phase CH 3 OCl from 200 to 460 nm. A study by Jungkamp et al 13 CH 4 + Cl f CH 3 12 The absorption spectrum exhibited two peaks in the UV range, one centered at 235 nm and a weaker one peaking at 310 nm. Crowley et al 12 calculated a photolysis rate constant of 6.8 × 10 -5 s -1 at a pressure of 100 mbar and a zenith angle of 80°, resulting in a stratospheric lifetime for CH 3 OCl of 4.1 h. The addition of perturbed ozone conditions (i.e., gas concentrations typical of the development of an ozone hole) into this simulation was not found to alter the photolysis rate constants greatly, as the 310 nm peak was responsible for the bulk of atmospheric photodissociation.…”
Section: Introductionmentioning
confidence: 99%